2018
DOI: 10.1055/s-0038-1675243
|View full text |Cite
|
Sign up to set email alerts
|

Normal Range for Maternal Lactic Acid during Pregnancy and Labor: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Objective This article systematically reviews the literature to establish the normal range of lactic acid in healthy pregnant women. Study Design Ovid MEDLINE, Embase.com, and Clinicaltrials.gov were searched to identify studies that reported maternal lactic acid in healthy pregnant women. Pooled aggregate means and two standard deviations for each time period were computed using the inverse variance weighting technique. Analyses were performed separately for 1st, 2nd, and 3rd trimesters, scheduled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Maternal blood lactate and pyruvate levels are also relatively consistent across trimester 3. 87, 88 Further, error in measurement introduced by single samples would tend to bias estimates towards the null. While, for most mothers, phthalate urinary metabolites were measured later in trimester 3 than the maternal serum metabolites, adjustment for this time interval had little effect and the strength of association between phthalate levels and pathway scores did not materially differ by time interval between serum and urine measures.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal blood lactate and pyruvate levels are also relatively consistent across trimester 3. 87, 88 Further, error in measurement introduced by single samples would tend to bias estimates towards the null. While, for most mothers, phthalate urinary metabolites were measured later in trimester 3 than the maternal serum metabolites, adjustment for this time interval had little effect and the strength of association between phthalate levels and pathway scores did not materially differ by time interval between serum and urine measures.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta‐analysis of observational studies by Bauer et al 25 reported that the maternal concentration of serum lactate outside of labor was less than 2 mmol/L, and that during labor periods, the range was higher than 2 mmol/L. While the pooled ranges were less than 4 mmol/L, few individual studies reported ranges higher than 4 mmol/L during labor.…”
Section: Discussionmentioning
confidence: 99%
“…20 While venous lactic acid levels can be used as a screening tool for infection in pregnant women, elevations may be seen during labor, especially later in labor when there is maximal skeletal muscle contraction. 21 Therefore, lactate alone may not be a reliable marker for the detection of infection at the time of intrapartum fever.…”
Section: The Road Map Forwardmentioning
confidence: 99%